2019
DOI: 10.1556/650.2019.31440
|View full text |Cite
|
Sign up to set email alerts
|

Speciális májműtét (Associating Liver Partition and Portal vein ligation for Staged hepatectomy, ALPPS) morbiditásának csökkentése átértékelt betegkiválasztási elvek és műtéttechnikai módosítás révén

Abstract: Introduction: Resecability of liver tumors is exclusively depending on the future liver remnant (FLR). The remnant can be hypertrophised using portal vein occlusion techniques. The latest hypertrophising method is Associating Liver Partition and Portal vein ligation for Staged hepatectomy (ALPPS), which provides the most significant induced hypertrophy in the shortest time. Morbidity and mortality of this procedure were initially unacceptably high. Aim: Reducing complications by better patient selection and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…Wajswol et al (Wajswol et al 2018) reported that 76% of PVE candidates underwent surgical resection. A 20% drop-out rate after first stage resection from disease progression was reported in another two-stage hepatectomy series (Narita et al 2011;Hahn et al 2019). In central bile duct tumors, a 25% rate of nonresectability has been reported in a larger series by Ebata et al (Ebata et al 2012).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Wajswol et al (Wajswol et al 2018) reported that 76% of PVE candidates underwent surgical resection. A 20% drop-out rate after first stage resection from disease progression was reported in another two-stage hepatectomy series (Narita et al 2011;Hahn et al 2019). In central bile duct tumors, a 25% rate of nonresectability has been reported in a larger series by Ebata et al (Ebata et al 2012).…”
Section: Discussionmentioning
confidence: 83%
“…Another group reported severe morbidity (Clavien- Dindo ≥3a) to occur in 50% (3/6) of the rescue ALPPS, 71% (10/14) of the ALPPS, and 38% (13/34) of the TSH/PVE patients ( p = 0.300) (Narita et al 2011 ). Consequently, for example Hahn et al, (Hahn et al 2019 ) modified their surgical strategy and reported a Clavien-Dindo III-IV morbidity of 22% and mortality of 0%.…”
Section: Discussionmentioning
confidence: 99%
“…10 A rendkívül magas reszekciós arány ellenére a szövődmények lehetősége miatt az eljárás csak szoros feltételek mellett történő betegszelekció után végezhető. Az eljárás kidolgozásában, a szövődmény arányának csökkentésében, a műtéti technika módosításában klinikánk világviszonylatban is vezető szerepet játszik [11][12][13] Ennek standard eljárása a 70-es évek elejére alakult ki: 2 × 30 perc, közte 2-3 perces szünet "fl ush" perfúzióval. Évente 20-30 jelentősebb májreszekció történt.…”
Section: A Modern Korunclassified